Non-syndromic enlarged vestibular aqueduct caused by novel compound mutations of the SLC26A4 gene: a case report and literature review - Huang, Yunhua; Li, Linlin; Pan, Liqiu; Ling, Xiaoting; Wang, Chenghan; Huang, Chaoyu; Huang, Yifang (Frontiers in Genetics, 2023)
Enlarged vestibular aqueduct (EVA) is an autosomal genetic disease mainly caused by mutations in the SLC26A4 gene and includes non-syndromic and syndromic types.This study aimed to identify genetic defects in a Chinese patient with non-syndromic enlarged vestibular aqueduct (NSEVA) and to investigate the impact of variants on the severity of NSEVA. A male patient, aged about 6 years, with NSEVA was recruited for this study. The clinical characteristics and results of auxiliary examinations, including laboratory and imaging examinations, were collected, and 127 common hereditary deafness genes were detected by chip capture high-throughput sequencing.Protein structure predictions, the potential impact of mutations, and multiple sequence alignments were analyzed in silico. Compound heterozygote mutations c.1523_1528delinsAC (p.Thr508Asnfs*3) and c.422T>C (p.Phe141Ser) in the SLC26A4 gene were identified. The novel frameshift mutation c.1523_1528delinsAC produces a severely truncated pendrin protein, and c.422T>C has been suggested to be a disease-causing mutation. Therefore, this study demonstrates that the novel mutation c.1523_1528delinsAC in compound heterozygosity with c.422T>C in the SLC26A4 gene is likely to be the cause of NSEVA. Cochlear implants are the preferred treatment modality for patients with NSEVA and severe-to-profound sensorineural hearing loss (SNHL). Genetic counseling and prenatal diagnosis are essential for early diagnosis. These findings expand the mutational spectrum of SLC26A4 and improve our understanding of the molecular mechanisms underlying NSEVA.